Exploring the Relationship between Early Leaving of Education and Training and Mental Health among Youth in Spain - Laura M. Guerrero-Puerta; Miguel A. Guerrero (Societies, 2023)
This study aimed to explore the relationship between Early Leaving Education and Training and mental health perceived by young Spanish school leavers, as well as develop mid-range theories to better understand this relationship. The study uses a grounded theory approach; specifically, Charmaz’s constructivist approach and its informed version have guided the study. Through qualitative interviews with individuals who had left school prematurely, the results of this study showed a bidirectional relationship between ELET and mental health, where the detriment in the mental health of young people who leave school early should be understood as both a cause and an effect of the process of ELET. In addition, the findings suggest that certain socio-economic and educational factors, such as bullying, academic stress, self-responsibilization of failure, and labels such as “NEET” can contribute to a decrease in mental health. Overall, this study has provided new insights into the ELET-mental health relationship, contributing to the development of mid-range theories that can inform future research and interventions to minimize these problems.